2020
DOI: 10.1016/j.adolescence.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and sexual risk‐taking: The interplay of constraining relationship beliefs, healthy sex attitudes, and romantic attachment insecurity

Abstract: Introduction: Although sexual exploration during adolescence may be perceived as normative, many adolescents who are sexually active are likely to engage in risky sexual behaviors detrimental to their well-being. The present study examined the influence of insecure attachment (anxious and avoidant dimensions), healthy sex attitudes, and constraining relationship beliefs on the following sexual risk indicators: age at first sex, number of sexual partners, condom use, length of time knowing sexual partners, seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 97 publications
(153 reference statements)
0
11
0
Order By: Relevance
“…Within this framework, anxious attachment is feeling overly dependent on the relationship partner to meet emotional needs, whereas avoidant attachment involves evading closeness with a romantic partner, often due to worry of losing independence or fear of rejection (Brennan et al, 1998). These dimensions of romantic attachment insecurity are linked to adolescents' sexual risk-taking, such as low condom use during intercourse (Feeney et al, 2000;Saint-Eloi Cadely et al, 2020) and cumulative sexual risk-taking (McElwain et al, 2015). Romantic attachment insecurity affects how adolescents think about themselves and their close relationships (Kerpelman et al, 2012;Pittman et al, 2011;Schachner & Shaver, 2004), which is associated with their decisions around sexual activity (Davis et al, 2004;Feeney et al, 2000;Saint-Eloi Cadely et al, 2020;Tracy et al, 2003).…”
Section: Framework For Understanding Adolescents' Sexual Risk Indicatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within this framework, anxious attachment is feeling overly dependent on the relationship partner to meet emotional needs, whereas avoidant attachment involves evading closeness with a romantic partner, often due to worry of losing independence or fear of rejection (Brennan et al, 1998). These dimensions of romantic attachment insecurity are linked to adolescents' sexual risk-taking, such as low condom use during intercourse (Feeney et al, 2000;Saint-Eloi Cadely et al, 2020) and cumulative sexual risk-taking (McElwain et al, 2015). Romantic attachment insecurity affects how adolescents think about themselves and their close relationships (Kerpelman et al, 2012;Pittman et al, 2011;Schachner & Shaver, 2004), which is associated with their decisions around sexual activity (Davis et al, 2004;Feeney et al, 2000;Saint-Eloi Cadely et al, 2020;Tracy et al, 2003).…”
Section: Framework For Understanding Adolescents' Sexual Risk Indicatorsmentioning
confidence: 99%
“…Noncommitted partnerships can include being in one or more casual relationships that are not viewed as exclusive or serious, whereas committed partnerships typically are exclusive and monogamous (Olmstead, 2020; Whitton et al, 2013). Emotions and social cognitions associated with experiences in romantic and sexual relationships matter for the riskiness of adolescents' sexual engagement (Manning et al, 2006; McElwain et al, 2015; Saint‐Eloi Cadely et al, 2020), and adolescents in noncommitted sexual relationships have been shown to have higher odds of experiencing negative mental health outcomes including depression and low self‐esteem (Manning et al, 2014), as well as negative romantic experiences in young adulthood (Manning et al, 2014; S. Shulman et al, 2020). Compared with adolescents in committed romantic relationships, the risk of unplanned pregnancies and sexually transmitted infections is higher when adolescents engage in sexual activity within noncommitted partnerships (Claxton & van Dulmen, 2013; Gurvey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations